Impact of Caregiving on Various Aspects of the Lives of Caregivers - Irfan, Babar (Cureus, 2017)
OBJECTIVE: This study was designed to assess the impact of caregiving on the lives of the caregivers. METHODS: A cross-sectional study was conducted between July and September 2015 at a teaching hospital in Karachi, Pakistan. Participants who were more than 18 years old and were involved in caregiving (former or current) of a family member were invited to participate in the study. The participants were recruited through consecutive sampling technique. A total of 400 caregivers were interviewed. Written informed consent was obtained from all the participants. A pretest structured questionnaire was used for data collection and included sections on demographic details and impact of caregiving on various aspects of the lives of caregivers. The data was analyzed using SPSS version 19 (IBM, NY, USA). RESULTS: Information about a total of 400 caregivers (215 men and 185 women) was included in the final analysis. The majority (57.0%) of the participants were aged between 18 and 30 years. About three-fifths (60%) of the participants were single and the majority of the participants were students. Approximately 64% of the participants were currently involved in caregiving and about 48% of the participants responded that caregiving has an overall negative impact on various aspects, such as physical (40.8%), psychological (47.8%), and professional aspects (51.8%) of their lives. CONCLUSION: Negative impact of caregiving was observed among caregivers due to extensive demands of caregiving and limited resources. Therefore, it is imperative for health care providers to explore, identify and support caregivers to cope in a better way to the challenging task of caregiving.